2017
DOI: 10.1155/2017/2618020
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Partial Replacement of Wheat Flour with Whey and Soy Protein on Rheological Properties of Dough and Cookie Quality

Abstract: The development of wheat-based foods that are enriched with proteins is increasingly popular. The purpose of this study was to compare the effects of partial replacement of wheat flour with whey and soy proteins (0–30%) on the rheological properties of dough and cookie-making quality. The incorporation of whey protein (WP) diluted the concentration of gluten, leading to an increase in dough development time (MDT) and breakdown torque and a decrease in stability time (MST) and minimum torque (MMT). The gelation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 26 publications
10
41
1
2
Order By: Relevance
“…The amount of inclusion levels of SFPC on LGWF slightly affecting the color of produced biscuits (Figure 4). The current result is in harmony with other workers [1,52,53,63].…”
Section: Effect Of Mixing Ratio On Color Parameters Of Upper and Lowesupporting
confidence: 92%
See 2 more Smart Citations
“…The amount of inclusion levels of SFPC on LGWF slightly affecting the color of produced biscuits (Figure 4). The current result is in harmony with other workers [1,52,53,63].…”
Section: Effect Of Mixing Ratio On Color Parameters Of Upper and Lowesupporting
confidence: 92%
“…However, textural properties of biscuits did not affect as protein and fat content increases. Similar results were reported by Chauhan et al [50] and Tang and Liu [52]. It was found that hardness of biscuit decreased…”
Section: Biscuit Physical Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…SPI enrichment increased the stickiness, floury mouthfeel, and compactness of rye breads, which appeared to decrease the acceptance of more than half the consumers. The sensory changes caused by SPI might be because the soy protein conferred a protective network on partial gluten structure which increased the dense and sticky texture of the dough and bread [ 15 , 46 ]. Enrichment with the blend of WPI/WPH and SPI counteracted each other’s effects on rye bread texture and contributed to consumer liking.…”
Section: Discussionmentioning
confidence: 99%
“…Höglund et al [ 14 ] reported that off flavors were detected for muffins with extra whey protein. Tang and Liu [ 15 ] found that the addition of whey protein disrupted the gluten structure of wheat dough and affected cookie texture negatively. On the contrary, soy protein conferred a protective network on partial gluten structure which increased the overall acceptability of the cookies.…”
Section: Introductionmentioning
confidence: 99%